Вербальні та невербальні засоби актуалізації непрямої респонсивної реакції адресата в англомовному побутовому дискурсі - Устименко, Світлана Євгеніївна (Харківський національний університет ім. В. Н. Каразіна, 2016)
Стаття присвячена дослідженню вербальних та невербальних засобів актуалізації непрямої респонсивної реакції адресата в англомовному побутовому дискурсі. Виявлено, що порушення прагматичної кореляції «питання – пряма відповідь», а саме відсутність репліки-реакції з прямою відповіддю на квеситивний мовленнєвий акт адресанта, актуалізується у структурі діалогічного дискурсу шляхом мікро- та макровзаємодії вербальних і невербальних компонентів комунікації. Установлено, що мікровзаємодія невербальних компонентів комунікації з вербальною складовою у респонсивній репліці адресата при униканні прямої відповіді відбувається за принципом координації, субординації та ідентифікації. Взаємодія вербальних і невербальних компонентів комунікації на макрорівні демонструє здатність непрямої невербальної реакції адресата на репліку-стимул адресанта повністю замінювати пряму вербальну відповідь адресата. У роботі висвітлюються комунікативно-прагматичні інтенції адресата при наданні непрямої відповіді в побутовому дискурсі. Стаття віддзеркалює важливість дискурсивної компетенції мовної особистості при виборі вербального або невербального оформлення респонсивної реакції відповідно до комунікативного наміру в межах певної комунікативної ситуації. Стаття демонструє важливість належної інтерпретації невербальних засобів комунікації, що сприяє ефективності процесу спілкування та вирішує проблему мовної економії.

Verbal and Non-verbal Means of Actualization of an Addressee’s Indirect Responsive Reaction in the English Everyday Discourse. The article deals with the study of verbal and non-verbal means of actualization of an addressee’s indirect responsive reaction in the English every day discourse. The paper finds out that the violation of the “question – direct answer” correlation that is the absence of the reactive utterance with a direct answer to a quesіtive speech act, is actualized in the structure of the dialogical discourse by the interaction of verbal and non-verbal means of communication at the micro- and macrolevels. The microinteraction of verbal and non-verbal communicative components in the addressee’s responsive reaction while avoiding a direct answer is realized on the principle of coordination, subordination and identification. The interaction of verbal and non-verbal means of communication at the macrolevel demonstrates the ability of the addressee’s indirect non-verbal reaction to the addresser’s utterance-stimulus to fully replace the addressee’s direct verbal answer. The paper investigates the addressee’s communicative and pragmatic intentions while providing an indirect answer in the everyday discourse. The article reflects the importance of a personality’s discursive competence while choosing a verbal or non-verbal design of a responsive reaction according to a communicative intention within a certain communicative situation. The article demonstrates the importance of proper non-verbal means of communication interpretation which promotes the efficiency of the communication process and solves the problem of linguistic economy.
Verbal and Non-verbal Means of Actualization of an Addressee’s Indirect Responsive Reaction in the English Everyday Discourse
Keywords: іноземні мови; адресат; дискурсивна компетенція; макровзаємодія; мікровзаємодія; невербальні компоненти комунікації; непряма відповідь; побутовий дискурс; addressee; non-verbal means of communication; macrointeraction; microinteraction; indirect answer; everyday discourse; discursive competence